Pengaruh Pemberian Lozenges Kombinasi Kulit Pisang dan Kulit Nanas terhadap Tikus Putih (Rattus norvegicus L.) galur Wistar - Adelita Ahyanurri; Liza Pratiwi; Hadi Kurniawan; Inarah Fajriaty; Siti Nani Nurbaeti; Nugraha Fajar; Pratiwi Apridamayanti (State University of Gorontalo, 2022)
Banana peel and pineapple peel have high potassium content. The banana peel and pineapple peel combination can be used as lozenges in potassium supportive therapy. The safety of banana peel and pineapple peel combination lozenges must be ensured by the acute toxicity test. One of the parameters observed during toxicity testing is the organ index. This study aims to determine the relationship between dose and toxicity in acute oral administration of banana peel and pineapple peel combination lozenges on the heart, lungs, liver, spleen, and kidneys organ index in white rats (Rattus norvegicus L.) Wistar strain. Acute toxicity based on OECD 425 guidelines for the Up-and-Down Procedure (UDP) method. Rats were grouped into 2000 mg/kg BW and 5000 mg/kg BW dose groups, consisting of 5 rats. Organ indexes were analyzed using SPSS Independent Sample T-test with 95% confidence level (p0.05). The result showed no significant difference between both doses (P0.05) in heart, lungs, liver, spleen, and kidneys organ index. Based on the results, it can be concluded that banana peel and pineapple peel combination lozenges did not affect white rats’ heart, lungs, liver, spleen, and kidney organ index.